Bibliografie van de geschiedenis van België = . Bibliographie de l'histoire de Belgique (Nauwelaerts)
[1]: 1789 - 21 juillet 1831 / Paul Gérin. 1960, 430 p. [2]: 1831-1865 / Solange Vervaeck. 1965, 304 p. [3]: 1865-1914 / J. de Belder, J. Hannes. 1965, 303 p. Avec index.